Characteristics and Insecticidal Potential of Ecoenzymes Derived from Vegetable Waste and Various Sugars - Dita Megasari; Wiwin Windriyanti; Mandayu Anestesia Hayyu Palupi; Anisah Qurrotu Aini; Nolla Dwi Elvira; Syaiful Khoiri (Institut Pertanian Bogor, 2026)
Vegetable waste is the second largest category of household organic waste, following grains. Its underutilization at the household level is an environmental concern, but it also has potential as a raw material for ecoenzyme synthesis. Ecoenzymes created by fermentation may be used as environmentally friendly alternatives to chemical pesticides. However, only a few research have investigated the effect of various sugar types on the insecticidal efficiency of ecoenzymes generated from vegetable waste. The goal of this study was to create ecoenzymes from vegetable waste and assess their insecticidal properties. Ecoenzymes were prepared using a 3:1:10 ratio of vegetable waste, sugar, and water. The vegetable waste comprised of cabbage, lemongrass, and red onion peels, while the sugars were molasses, brown sugar, and granulated sugar, resulting in nine different compositions. Fermentation lasted three months. Each 10% ecoenzyme solution was tested for insecticidal activity against Crocidolomia pavonana larvae in their second instar stage. All ecoenzyme formulations exhibited physical characteristics associated with successful fermentation, such as an acidic pH (3.1−3.6), dark brown coloration, and a strong sour fragrance. Bioassays revealed that ecoenzymes had insecticidal effects through larval mortality and feeding inhibition. The mixture with lemongrass and molasses had the highest mortality (66.67%) and strongest antifeedant effect. Variations in waste type and sugar supply have a substantial impact on ecoenzyme performance. The findings demonstrate that vegetable waste may be effectively transformed into ecoenzymes with insecticidal characteristics, indicating their potential for application in sustainable pest management. Keywords: Crocidolomia pavonana, organic waste, plant-based pesticide, sustainable agriculture